Pendekatan Inklusif dalam Perancangan Ulang Interior Taman Kanak-Kanak - Arnanti Primiana Yuniati; Athifa Sri Ismiranthi; Firza Tsabit Haryono; Tengku Naufal Alriza; Tartila Dinda Prasetyo; Athayasany Thalita Arundati; Aulia Amanda (Aliansi Desainer Produk Industri Indonesia (ADPII), 2026)
Kindergarten functions as a place that supports the development of early childhood as a whole, both regular and special needs. Children's development is the physical, intellectual, moral, and creative aspects of children to be ready to enter further education. However, in practice, the needs of early childhood have not been accommodated in educational facilities, such as in the case study of the Bunda Asuh Nanda Kindergarten interior space, Arcamanik branch, Bandung. The research method adapts two design thinking process models divided into problem (empathy and problem identification) and solution (ideation, prototype, and test) sections. It is supported by divergent and convergent thinking. These problems include the need for kindergarten spaces adapted to the 2020 Merdeka Belajar Curriculum, inclusive design for ASD (Autism Spectrum Disorder) level 1 students, and the lack of privacy in the principal's room. The solution offered is to design the kindergarten space by using learning activities and curriculum while adapting to the needs of regular and special children. The concept is minimalist, modular and multi-sensory. The application of the concept is in the form of table positioning according to children's talent groups, storage locker facilities for each child, multi-sensory play areas, provision of facilities for students with special needs such as ASD corner, and separating the principal's room which is still combined with the Kindergarten B room by providing folding partitions to separate them as needed. The design thinking process requires two-way communication between the designer and the client and an iterative process to reach a design agreement.